Recent advances in the theoretical studies on the electrocatalytic CO2 reduction based on single and double atoms - Meng, Yuxiao; Huang, Hongjie; Zhang, You; Cao, Yongyong; Lu, Hanfeng; Li, Xi (Frontiers in Chemistry, 2023)
Excess of carbon dioxide (CO2) in the atmosphere poses a significant threat to the global climate. Therefore, the electrocatalytic carbon dioxide reduction reaction (CO2RR) is important to reduce the burden on the environment and provide possibilities for developing new energy sources. However, highly active and selective catalysts are needed to effectively catalyze product synthesis with high adhesion value. Single-atom catalysts (SACs) and double-atom catalysts (DACs) have attracted much attention in the field of electrocatalysis due to their high activity, strong selectivity, and high atomic utilization. This review summarized the research progress of electrocatalytic CO2RR related to different types of SACs and DACs. The emphasis was laid on the catalytic reaction mechanism of SACs and DACs using the theoretical calculation method. Furthermore, the influences of solvation and electrode potential were studied to simulate the real electrochemical environment to bridge the gap between experiments and computations. Finally, the current challenges and future development prospects were summarized and prospected for CO2RR to lay the foundation for the theoretical research of SACs and DACs in other aspects.